Weight and metabolic changes in early psychosis-association with daily quantification of medication exposure during the first hospitalization - Vochoskova, Kristyna; McWhinney, Sean R; Fialova, Marketa; Kolenic, Marian; Spaniel, Filip; Svancer, Patrik; Boron, Petra; Okaji, Yurai; Trancik, Pavel; Hajek, Tomas (Acta psychiatrica Scandinavica, 2023)
BACKGROUND: The most common causes of death in schizophrenia are cardiovascular disorders, which are closely related to metabolic syndrome/obesity. To better understand the development of metabolic alterations early in the course of illness, we quantified daily medication exposure in the first days of the first hospitalization for psychosis and related it to changes in weight and metabolic markers. STUDY DESIGN: We recruited participants with first episode psychosis (FEP, N = 173) during their first psychiatric hospitalization and compared them to controls (N = 204). We prospectively collected weight, body mass index, metabolic markers, and exact daily medication exposure at admission and during hospitalization. STUDY RESULTS: Individuals with FEP gained on average 0.97 ± 2.26 BMI points or 3.46 ± 7.81 kg of weight after an average of 44.6 days of their first inpatient treatment. Greater antipsychotic exposure was associated with greater BMI increase, but only in people with normal/low baseline BMI. Additional predictors of weight gain included type of medication and duration of treatment. Medication exposure was not directly related to metabolic markers, but higher BMI was associated with higher TGC, TSH, and lower HDL. Following inpatient treatment, participants with FEP had significantly higher BMI, TGC, prolactin, and lower fT4, HDL than controls. CONCLUSION: During their first admission, people with FEP, especially those with normal/low baseline BMI, showed a rapid and clinically significant weight increase, which was associated with exposure to antipsychotics, and with metabolic changes consistent with metabolic syndrome. These findings emphasize weight monitoring in FEP and suggest a greater need for caution when prescribing metabolically problematic antipsychotics to people with lower BMI.
Keywords: psychotické poruchy; schizofrenie; dospělí; antipsychotics; dyslipidemia; index tělesné hmotnosti; Humans; Metabolism; mladý dospělý; Body Mass Index; mužské pohlaví; antipsychotika; schizophrenia; first episode psychosis; Adult; metabolismus; Adolescent; hospitalizace; sekundární prevence; hmotnostní přírůstek; Hospitalization; biologické markery; Secondary Prevention; Psychotic Disorders; ženské pohlaví; Antipsychotic Agents; poměr pasu a boků; lidé; mladiství; Schizophrenia; Weight Gain; Biomarkers; Male; Young Adult; Waist-Hip Ratio; cholesterol; Female